The structural and spatial properties of the high-speed railway network in China: A complex network perspective. (May 2019) - Cao, Weiwei; Feng, Xiangnan; Zhang, Hong
Abstract: High-speed railway (HSR) has been one of the most important transport modes for developing cities. The development and achievement of HSR in China has attracted attention from around the world. Previous studies on HSR primarily focused on its impacts on regional development, the environment and the socio-economy. The structural and spatial properties of the HSR network have been neglected if not all. This article takes China's high-speed railway network (CHSRN) as an example and converted it into a weighted network using a P-space approach. The structural and spatial properties of CHSRN at the node and network levels are explored. The degree, strength and betweenness centralities of cities in CHSRN are calculated and analyzed. An integrated indicator based on the centrality measures is proposed to quantify the overall role of each city in CHSRN. The small-world property of CHSRN is examined, and the scale-free, spatial heterogeneity and hierarchical properties of CHSRN are examined in terms of train flow intensity. Possible factors affecting the structure and spatial properties of CHSRN are also explored. Highlights: This study provides a comprehensive analysis on structural and spatial properties of CHSRN at the city-level. We highlighted that the most connected nodes may not be the most central ones in CHSRN because of possible geographical, economic and political reasons. An integrated indicator is proposed. The integrated indicator helps to classify CHSRN into a multi-layer network. Strong connections between different layers in CHSRN are identified via the new indicator. We evaluated the small-world and scale-free properties along with spatial heterogeneity and hierarchies of CHSRN.